PENGARUH KREDIBILITAS DAN DAYA TARIK INFLUENCER TERHADAP PERILAKU MINAT BELI KONSUMEN DI MEDIA SOSIAL - Derline Sugiarto; Farid Raka Jamaludin; Muhammad Divo (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2026)
Social media has become an effective digital marketing platform for influencing consumer behavior through the use of influencers as promotional agents. Influencers' credibility and attractiveness are considered important factors that shape consumer perceptions and encourage purchase intention behavior. This study aims to analyze the influence of influencer credibility and attractiveness on consumers' purchase intention behavior on social media. This study employed a quantitative research approach using a survey method. The population consisted of social media users who had been exposed to product promotions delivered by influencers, while the sample comprised 62 respondents selected through purposive sampling. Data were collected using a structured questionnaire and analyzed with IBM SPSS Statistics version 27 through validity and reliability tests, multiple linear regression analysis, partial (t) tests, simultaneous (F) tests, and coefficient of determination analysis. The independent variables were influencer credibility (X₁) and influencer attractiveness (X₂), whereas the dependent variable was consumers' purchase intention behavior (Y). The findings indicate that both influencer credibility and attractiveness have a positive and statistically significant effect on consumers' purchase intention behavior, both individually and simultaneously. The coefficient of determination shows that the two independent variables explain 64.4% of the variance in consumers' purchase intention behavior. These findings suggest that influencer credibility and attractiveness play an important role in encouraging consumers' purchase intention behavior on social media and can therefore serve as strategic considerations for businesses in developing more effective digital marketing initiatives.